Pengembangan Media Pembelajaran Online App Builder "Appypie" Berbasis Android pada Materi Program Linear - Rachmalia Vinda Kusuma; Mohammad Nurwahid; Yenny Fitria Novitasari (ARITHMETIC: Academic Journal of Math, 2024)
This research is motivated by the lack of use of learning media in mathematics learning, which causes students' interest in learning and activeness to remain low, thus affecting students' learning outcomes. The aim of this research is to develop learning media for Android-based App-Builder Online "Appypie" that is valid, practical, and effective so that it can be used in mathematics learning, especially in linear programming material. This research is development research using the 4-D model, namely Define, Design, Develop, and Disseminate. The product developed in this research is an Android-based application. This research was carried out at SMKN 2 Tuban with the research subjects being 25 students of class XI-Accounting-2. The data collection instruments used were validation sheets, interview guidelines, observation sheets, and response questionnaires. Data analysis used was validation tests, practicality tests, and effectiveness tests. The validation results were 85.30% with a very valid category. The practicality test results were 89.75% in the very practical category. The effectiveness test results were 84% in the effective category. Based on the results of this research, it was concluded that the development of the online app builder "Appypie" produced a product in the form of Android-based learning media on Linear Program material which met the criteria of being valid, practical, and effective for use in mathematics learning.